Animated Life Writing - Petryna, Brandon (Imaginations: Journal of Cross-Cultural Image Studies, 2023)
<span style="caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;">This paper proposes that the medium of animation enriches the narrative portrayal of lived experiences. Despite the rise in popularity of animation as a tool for storytelling on digital video sharing platforms, as of yet, little scholarship explores the impacts of animation on life writing narratives. In an encounter with animation production, I develop an original example of these animated narratives which I term <em style="-webkit-print-color-adjust: exact; caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">animated life writing<span style="caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;">. Through the approaches of critical making and research in practice, by which I have created an <a style="-webkit-print-color-adjust: exact; color: #4183c4; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" href="https://www.youtube.com/watch?v=24WaFML4TjU">accompanying animated video<span style="caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;">, the benefits and drawbacks of animation are explored with a particular focus on embodiment in life writing and the liveliness that is generated by cartoons.